PENGARUH ETIKA LINGKUNGAN PERUSAHAAN TERHADAP KEUNGGULAN KOMPETITIF: PERAN MEDIASI INOVASI PRODUK HIJAU - Pemayun, Anak Agung Istri Cintya Dewi; Suprapti, Ni Nyoman Sri (E-Jurnal Manajemen, 2016)
This study empirically explores green product innovation in mediating the effects of environmental ethics of corporate to a competitive advantage. Data were collected from 100 respondents of The Body Shop cosmetics users in Denpasar using a questionnaire instrument. Data were analyzed using descriptive and inferential path analysis. The results showed that the environmental ethics corporate significant affect the innovative green products, environmental ethics corporate significant affect the competitive advantage, green product innovation significant affect the competitive advantage, green product innovation significant mediates the relationship of environmental ethics of corporate to a competitive advantage
Keywords: ethics corporate environment, green product innovation, and competitive advantage